A soil classification for seismic hazard assessment and mitigation of the Algarve - Carvalho, João P. F. (2008)
The Algarve province of Portugal is located near the E-W Eurasia-Africa plate boundary. It is characterized by a moderate seismicity, with some important historical earthquakes causing important damage and economical losses. Not only has it suffered the effects of large plate boundary events but also the impact of local onshore moderate-sized earthquake sources. The seismic hazard evaluation and mitigation of the area is therefore of great importance to the local populations and the large number of tourists that frequent the region. This paper focuses the evaluation of the most interesting and useful geotechnical near-surface parameters and a soil classification. The classification based upon the European Code 8 for civil engineering and SPT bedrock data, was carried out for land use planning and design of critical facilities. P-wave and S-wave seismic velocities were obtained through the acquisition, processing and interpretation refraction profiles. Hundreds of SPT parameters from available boreholes drilled for engineering and water supply were used and subsoil classification based on geophysical and geotechnical parameters is presented. Other parameters, such as Vp/Vs ratios and the Poisson coefficient were estimated and were computed to provide information for future site effect studies. The experimental procedure tested here is relatively fast, economical and easy to perform and can be useful to estimate soil microzoning and seismic hazard mapping in the absence of local earthquake records.